The social psychological processes of ‘procedural justice’: Concepts, critiques and opportunities - Radburn, Matthew (Criminology & criminal justice, 2019)
Contemporary research on policing and procedural justice theory (PJT) emphasizes large-scale survey data to link a series of interlocking concepts, namely perceptions of procedural fairness, police legitimacy and normative compliance. In this article we contend that as such, contemporary research is in danger of conveying a misreading of PJT by portraying a reified social world divorced from the social psychological dynamics of encounters between the police and policed. In this article we set out a rationale for addressing this potential misreading and explore how and why PJT researchers would benefit both theoretically and methodologically through drawing upon advances in theoretical accounts of social identity, developed most notably in attempts to understand crowd action. Specifically, we advance an articulation of a ‘process-based’ model of PJT’s underlying social and subjective dynamics and stress the value of ethnographic approaches for studying police-‘citizen’ encounters.